Where do the actants, mangles come from? - Jochen Gläser; Grit Laudel (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1999)
This paper deals with the methodological problem of how to include material influences in comparative studies of research processes. Both Actor-Network-Theory and ,Mangle-of-Practice` confirm convincingly enough that materiality must be taken into account in empirical investigations of research processes. However, it is not clear how material factors can be included systematically in comparative studies. In this paper, we use empirical examples from comparative institutionalist studies of research processes to discuss the difficulties that hinder comparative analyses. It turns out that neither Actor-Network-Theory nor ,Mangle` support comparative analyses of material influences. As causes for this deficiency, we discuss the treatment of materiality as situationally emergent phenomenon, the absence of methodology and the theoretical models` level of abstraction. A methodological framework is proposed that should support systematic comparative analyses. This framework rests on an understanding of materiality as a cognitive condition of action. With the concept of cognitive conditions of action, materiality can be introduced into theories of action and into institutionalist approaches. – – Gegenstand dieses Aufsatzes ist das methodologische Problem der Einbeziehung materieller Einflüsse in die vergleichende Untersuchung von Forschungsprozessen. Daß solche Einflüsse berücksichtigt werden müssen, kann angesichts der neueren Befunde des Konstruktivismus (Actor-Network-Theory und Mangle of Practice) kaum in Zweifel gezogen werden. Weitgehend offengeblieben ist aber bisher, wie eine systematische vergleichende Einbeziehung von Materialität erfolgen kann. In dem Paper werden anhand empirischer Beispiele aus vergleichenden institutionalistischen Studien die Schwierigkeiten diskutiert, die in einer vergleichenden Analyse entstehen. Dabei zeigt sich, dass weder Actor-Network-Theory noch ,Mangle' vergleichende Analysen materieller Einflüsse unterstützen. Als Ursachen werden die Behandlung materieller Einflüsse als rein situative Faktoren, das Fehlen einer Methodologie und der Abstraktionsgrad der theoretischen Modelle diskutiert. Als Ansatz für einen methodologischen Rahmen, der die systematische vergleichende Einbeziehung materieller Einflussfaktoren ermöglicht, wird deren Konzeptualisierung als kognitive Handlungsbedingungen vorgeschlagen. Dadurch kann die Verbindung zur Handlungstheorie und zu auf Handlungstheorien beruhenden institutionalistischen Ansätzen hergestellt werden.
Keywords: 300; Wissenschaftsforschung; Theorie